The Role of Judges Based on Considerations of Community Cultural Values to Create Justice - Handika Naufal Husni; Widayati Widayati (Universitas Islam Sultan Agung, 2021)
This paper discusses the role of judges based on the cultural values of the community in realizing justice. With the sociological juridical approach method, namely through the role of judges in court to realize justice. In realizing justice, judges apply the law based on a verdict and the judicial power law that judges have rights and a code of ethics which is specifically regulated in law. Regarding the culture of the community that still exists, it is hoped that the role of the judge is to actualize justice by putting in place a rule and implementing a decision with a legal background that exists in the community, namely customary law as an addition to a decision.